An extremely large saber-tooth cat skull from Uruguay (late Pleistocene–early Holocene, Dolores Formation): body size and paleobiological implications. Issue 2 (2nd April 2020) - Manzuetti, Aldo; Perea, Daniel; Jones, Washington; Ubilla, Martín; Rinderknecht, Andrés
Abstract: Among the three recognized species of Smilodon, S. populator is the largest in size and has the widest distribution across South America. The present contribution describes an almost complete skull assigned to the aforementioned felid. The material was recovered from sediments of the Dolores Formation (Lujanian Stage/Age) from the southern part of Uruguay. This specimen is remarkable for its unusual craniodental measurements, indicating that it is one of the largest known specimens of the genus. Estimates of body mass indicate that this individual weighed over 400 kg. In addition, maximum prey size estimation greatly surpasses 1 t and approach nearly 3 t. Based on this, aspects of the paleobiology and paleoecology of S. populator are discussed. Undoubtedly, this kind of carnivorous mammal was at the top of the food chain, with clear adaptations for feeding upon the largest available herbivores, which potentially includes several megafaunal mammal species found in South America during the late Pleistocene. Aldo Manzuetti [aldomanzuetti@adinet.com.uy ], Facultad de Ciencias (UdelaR), Iguá 4225, CP 11400, Montevideo, Uruguay; Daniel Perea [perea@fcien.edu.uy ], Facultad de Ciencias (UdelaR), Iguá 4225, CP 11400, Montevideo, Uruguay; Washington Jones [wawijo@yahoo.com.ar ], Museo Nacional de Historia Natural, 25 de Mayo 582, CP 11000, Montevideo, Uruguay; Martín Ubilla [ubilla@fcien.edu.uy ], Facultad de Ciencias (UdelaR), Iguá 4225, CP 11400, Montevideo, Uruguay; Andrés Rinderknecht [apaleorinder@yahoo.com ], Museo Nacional de Historia Natural, 25 de Mayo 582, CP 11000, Montevideo, Uruguay .